Calculating space control in association soccer through individualized Voronoi-cells using historic performance data - Rein, R.; Bajorat, A.; Ewers, M.; Memmert, D. (Sportinformatik XI : Jahrestagung der dvs-Sektion Sportinformatik 2016 in Magdeburg, 2016)
At present, tactical skill is increasingly being seen as the key property of successful coaches and individuals like Pep Guardiola or Diego Simeoni are praised for the tactical genius. Indeed, research confirms that tactical behavior is a crucial aspect for successful performance in modem association soccer (Kannekens, Elferink-Gemser, & Visscher, 2011; Memmert, Lemmink, & Sampaio, 2016). However, at present tactical analysis in a strict sense has seen much less attention in the literature compared to classical notational approaches investigating event sequences in soccer (Rein & Memmert, 2016). Following the insights by Garganta (2009), the tactics specify how a team manages space, time, and individual actions throughout a game (Fradua et al., 2013; Garganta, 2009). Thus, by changing the tactics a team can modify the way space is available for their team as well as for the opponent limiting attacking and defending opportunities. Consequently, this leads to the question of how space control can be quantified from a scientific point of view.